163k views
2 votes
Given that f(x) = x2 – 7x – 1, g(x) = 2x – 3, and h(x) = 4x – 5 find each function.

(f + g)(x)


options:

A) x2 – 5x – 4

B) x2 – 11x + 4

C) x2 – 3x – 6

D) x2 – 5x – 6

User Equiman
by
5.4k points

2 Answers

4 votes

Answer:a

Explanation:

User Marc Cals
by
4.8k points
4 votes

Answer:

A)

Explanation:

(f+g)(x) = f(x) + g(x)

now plug in the expressions of f(x) and g(x) :

(f+g)(x) =
x^(2) -7x-1 + 2x-3

we combine like terms we get :

(f+g)(x) =
x^(2) -7x+2x -1-3

we simplify we get :

(f+g)(x)=
x^(2) -5x-4

so the answer is A)

User Eudore
by
6.3k points